Anaerobic degradation of oleic acid by suspended and granular sludge : identification of palmitic acid as a key intermediate - Pereira, M. A. (2002)
The aim of the present work was to study the maximum potential methane production in batch assays of sludge samples taken along the operation of two EGSB reactors (RI inoculated with granular sludge and RII inoculated with suspended sludge) fed with increasing oleic acid concentrations between 2 and 8 gCOD/l (HRT = 1 day). After removing the residual substrate, the sludge was incubated in batch vials without any added carbon source. A maximum methane production rate of 152 ± 21 mlCH4(STP)/gVS.day was obtained for the suspended sludge taken on day 70, when oleate at a concentration of 2 g COD/l was fed with a co-substrate (50% COD). The maximum plateau achieved in the methane production curve was 1145 ± 307 mlCH4(STP)/gVS, obtained for the suspended sludge taken on day 162, when oleate was fed as the sole carbon source at 6 g COD/l. The methanization rate of the adsorbed substrate was enhanced under stirring conditions and was inhibited by adding oleic acid. Extraction and GC analysis confirmed that the main adsorbed substrate was palmitate, and not oleate. Accumulated palmitate adsorbed onto the sludge and further β-oxidation was inhibited when in the presence of oleic acid. If oleic acid was removed from the medium β-oxidation proceeded with methane production. Suspended sludge was more efficient than granular sludge.